Contribution to diagnostics/prognostics of tuberculosis in children. II. Indicative value of metal ions and biochemical parameters in serum - Luterotti Svjetlana; Kordić Tončica Vukman; Letoja Ivka Zoričić; Dodig Slavica (Acta Pharmaceutica)
Newly introduced methods of assaying simultaneously copper and zinc and zinc alone in serum by flame atomic-absorption spectrometry are simple and economical, especially in saving the consumption of serum material. Along with biochemical parameters, they have been successfully applied to diagnostics/prognostics of tuberculosis in children, through analyses of sera from pediatric patients with lung tuberculosis or suspected tuberculosis, enabling the follow-up of therapeutic efficiency. The prognostic strength of Cu and Cu/Zn ratio together with C-reactive protein, complement components C3 and C4, and erythrocyte sedimentation rate have been documented.